Implementasi Manajemen Peserta Didik dalam Meningkatkan Kualitas Lulusan di MAN 1 Labuhanbatu Utara - Sri Muliyani; Muhammad Rifa`i; Fitri Hayati (Jurnal Budi Pekerti Agama Islam, 2024)
Quality graduates need to be supported by good student management and maximum educational services so that the school is able to provide meaningful learning experiences for the growth and development of students. This research aims to determine the implementation of student management, the quality of graduates and the implementation of student management in improving the quality of graduates at MAN 1 Labuhan Batu Utara. The research methodology uses qualitative research methods. Data collection techniques obtained through observation, interviews, documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. Based on research conducted by MAN 1 Labuhan Batu Utara researchers in carrying out student management starting from planning, coaching and developing students to evaluating student activities, the school maximally provides the best service for students and implementing student management. at MAN 1 North Labuhan Batu is classified as very good. In improving the quality of graduates, they provide maximum guidance and coaching to students in order to get maximum results. Students who from the start have good potential are then managed or guided well at MAN 1 Labuhan Batu Utara so that they have a significant impact on students' learning achievements with the achievements achieved.